The Role of Leadership and Decision-Making under Crisis: A bibliometric analysis and scientific evolution from 1962 to 2020 - Harry Patria (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
The unprecedented importance of leadership and decision-making under recent pandemic and economic crises boosts the development of this research domain. This study shed light on the published works of leadership and decision-making under crises which have had the greatest contribution and evolutionary scientific paths over the decades, which are: (1) inspect the scientific anatomy of earlier works and their main structures; (2) scrutinize the scientific trends and the evolutionary path, and (3) recognize theoretical and practical implications. This study generates its analysis based on R programming language with a package of ‘bibliometrix’ (a) multidimensional data analysis, (b) intellectual structure and network analysis, (c) conceptual structure and factorial analysis, (d) strategic diagrams and evolution maps, and (e) historical citation network and research collaboration across the world. From this bibliometric study covering 692 articles published in the academic journal from 1962 to 2020, the findings open up an opportunity of how leaders overcome plausible crises by making the right decision through organizational resources, technological capability, people management. Subsequently, the findings can explain the way decisions are made so that prevent the potential crisis in the stage of planning and lessening the harm in the stage of crisis intervention. For theoretical contributions, it appears that future research needs to explore the emerging themes of data mining, artificial intelligence, information system, and information management. In the era of the COVID-19 pandemic, healthcare and crisis management are likely to be addressed by unleashing cutting-edge digital technology such as Artificial Intelligence (AI), Machine Learning (ML), and Internet of Things (IoT).